Encapsulation of glucose oxidase in Fe(III)/tannic acid nanocomposites for effective tumor ablation via Fenton reaction. (8th October 2019) - Du, Keke; Liu, Qianqian; Liu, Mei; Lv, Rongmu; He, Nongyue; Wang, Zhifei
Abstract: Increasing the content of reactive oxygen species (ROS) with the assistance of nanoformulations in cancer cells via the Fenton reaction is considered an effective method to treat cancer. However, the efficiency of the Fenton reaction is affected by the level of H2 O2, the selection of iron ions in different nanoformulations, etc. Herein, we use Fe III -tannic acid (Fe III TA) nanocomposites as the carrier to deliver glucose oxidase (GOD) which can solve the problem of insufficient endogenous H2 O2 by catalytically converting the glucose. In comparison with traditional Fe 2+ /Fe 3+, Fe III TA nanocomposites perform higher catalytic activity in converting H2 O2 to high toxic hydroxyl radicals (·OH) due to the TA-mediated reduction of Fe 3+ . So, the integration of GOD and TA in the construction of nanocomposites significantly enhances the efficiency of the Fenton reaction. In vitro experiments show that ·OH produced by GOD-Fe III TA nanocomposites can not only achieve a good anticancer effect at a low concentration but also promote degradability of the nanocomposites. When it is only 1.08 μ g · ml −1, the cell apoptosis rate has reached 76.91%. In vivo experiments further demonstrate that GOD-Fe III TA nanocomposites can significantly inhibit tumor growth. So this work lays a good foundation for Fenton reaction-based cancer treatment.